THE IMPORTANCE OF SOFT SKILLS DEVELOPMENT IN HUMAN RESOURCE MANAGEMENT - Rio Mattajang (SEAN Institute, 2023)
Soft skills, which include interpersonal skills, effective communication, leadership, and teamwork, play a crucial role in improving individual and organizational performance as a whole. Soft skills, which include interpersonal skills, effective communication, leadership, and teamwork, play a crucial role in improving individual and organizational performance as a whole. This research uses a qualitative approach with descriptive methods. The research results show that soft skills, such as communication skills, teamwork, creativity, adaptability and work ethic, have a crucial role in the world of work. Soft skills are not only an individual's innate character, but can also be learned through social interaction and self-awareness. The importance of developing soft skills is increasingly felt in human resource management in the era of workplace transformation. The direct impact of developing soft skills includes increased productivity, customer satisfaction, and constructive conflict management. The soft skills development strategy in HRM involves a holistic approach, from redesigning job descriptions to implementing psychometric tests. Behavioral interviews, skill development programs, and a culture of continuous learning are key in creating an environment where individuals continue to thrive. Overall, the integration of soft skills in HRM strategy is an important step to ensure a balance between technical skills and human skills in dealing with the complexity and dynamics of the modern workplace.